APAKAH HIPOTESIS â€œEXPORT LED GROWTHâ€ BERLAKU DI INDONESIA? - Sumiyarti, Sumiyarti (Jurnal Ekonomi & Studi Pembangunan, 2015)
Abstract: This study aimed to test whether the hypothesis of "export led growth" applies to the Indonesian economy. The term "export led growrth" refers to a situation where a country's exports become the motor of economic growth. To achieve these objectives research using data GDP (Y) as a proxy for economic growth and serve as the dependent variable, and manufacturing exports (X), capital goods imports (M), the stock of capital (K) and labor (L) as independent variables. Of all variables used, variable labor value or coefficient greatest. While variable manufacturing exports had the smallest coefficient. Although when compared with other control variabe, the role of manufacturing exports variable in influencing economic growth (GDP) is relatively small, but the statistical significance of the test results may indicate that the alleged hypothesis of "export led growth" applies in Indonesia can be accepted.Abstrak: Studi ini bertujuan untuk menguji apakah hipotesis â€œexport led growthâ€ berlaku untuk perekonomian Indonesia. Istilah â€œexport led growrthâ€ merujuk pada suatu keadaan dimana ekspor suatu negara menjadi motor penggerak pertumbuhan ekonomi. Untuk mencapai tujuan tersebut studi menggunakan data PDB (Y) sebagai proksi pertumbuhan ekonomi dan berlaku sebagai variabel dependen, serta ekspor manufaktur (X), impor barang modal (M), stok kapital(K) serta tenaga kerja (L) sebagai variabel independen. Dari seluruh variabel yang digunakan, variabel tenaga kerja memiliki nilai atau koefisien yang paling besar. Sedangkan variabel ekspor manufaktur memiliki koefisien yang paling kecil. Meskipun bila dibandingkan dengan variabel kontrol lainnya, peran variabel ekspor manufaktur dalam mempengaruhi pertumbuhan ekonomi (PDB) relatif sangat kecil, namun signifikansi hasil uji statistik dapat menunjukkan bahwa dugaan hipotesis â€œexport led growrthâ€ berlaku di Indonesia dapat diterima.